1997
DOI: 10.1007/s11661-997-0207-2
|View full text |Cite
|
Sign up to set email alerts
|

Shock-induced martensitic transformations in near-equiatomic NiTi alloys

Abstract: Shock-impact generated tensile-stress pulses were used to induce B2-to-monoclinic martensitic transformations in two near-equiatomic NiTi alloys having different martensite transformation start (M s ) temperatures. The NiTi-I alloy (M s Ϸ ϩ27 ЊC) impacted at room temperature at 2.0 and 2.7 GPa tensile stress-pulse magnitude, showed acicular martensite morphology. These martensite needles had a substructure containing microtwins, typical of ''stress-assisted'' martensite. The NiTi-II alloy (M s Ϸ Ϫ45 ЊC) showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 18 publications
(10 reference statements)
1
5
0
Order By: Relevance
“…This hypothesis is further supported by considering that in previous work studying NiTi alloys that were not precipitate strengthened, martensite was retained within similar intragranular microband features. [28] This hypothesis is also consistent with the bilinear release response seen in Figure 3b. Initially, elastic unloading of the loaded stress-induced martensite structure occurs, then, elastic unloading is accompanied by reverse martensitic transformation and/or plastic release.…”
Section: Resultssupporting
confidence: 88%
“…This hypothesis is further supported by considering that in previous work studying NiTi alloys that were not precipitate strengthened, martensite was retained within similar intragranular microband features. [28] This hypothesis is also consistent with the bilinear release response seen in Figure 3b. Initially, elastic unloading of the loaded stress-induced martensite structure occurs, then, elastic unloading is accompanied by reverse martensitic transformation and/or plastic release.…”
Section: Resultssupporting
confidence: 88%
“…It exhibits SE while the test temperature is close to the austenite finish temperature (A f ) [8][9][10][11][12][13][14]. A considerable body of experiments has been conducted on NiTi alloys to investigate its strain rate and temperature-dependent phase transformation behaviour [11,12,[14][15][16][17][18][19]. Nemat-Nasser et al [8,9] studied the dynamic behaviour of NiTi at various strain rates in a range of 10 −3 to about 2 × 10 4 s −1 and at temperatures in a range of 77-400 K. The results showed that the SE behaviour of NiTi was more sensitive to temperature than to strain rate.…”
Section: Introductionmentioning
confidence: 99%
“…martensitic transformations and crystal to amorphous phase transitions have also been studied. [11][12][13][14][15][16][17][18][19][20][21] Solid state structural phase transformations from low to high or from high to low density states have been considered to occur via reconstructive or displacive mechanisms. 22 Such displacive phase transformations involve coordinated shifts of atoms comprising of homogeneous strain and shuffle, and hence, are favoured under high pressure, while reconstructive transformations are less likely to occur at high pressures due to the reduced mobility of atoms.…”
Section: Introductionmentioning
confidence: 99%
“…15 SEM micrographs of recovered Nb+Si compacts revealing (a) an unreacted portion, (b) the transition zone between unreacted and partially-reacted material, (c) a partially-reacted region, and (d) the transition zone between partially-reacted and fully-reacted material. The reaction product consists of NbSi 2 nodules, which are concentrated near the Nb particle interfaces (from Vecchio et al 100 ).…”
mentioning
confidence: 99%